2017
DOI: 10.1038/s41598-017-04042-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of energetic ion irradiation on WSe2/SiC heterostructures

Abstract: The remarkable electronic properties of layered semiconducting transition metal dichalcogenides (TMDs) make them promising candidates for next-generation ultrathin, low-power, high-speed electronics. It has been suggested that electronics based upon ultra-thin TMDs may be appropriate for use in high radiation environments such as space. Here, we present the effects of irradiation by protons, iron, and silver ions at MeV-level energies on a WSe2/6H-SiC vertical heterostructure studied using XPS and UV-Vis-NIR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…The synthesis strategies [93][94][95][96] devoted to the preparation of 2D heterostructures could be classified into three main kinds, including exfoliation and transfer method, [97,98] chemical vapor deposition (CVD) method, [99,100,101] and physical vapor deposition method (PVD). [29] The exfoliation and transfer method is dedicated to the exploration of vertical 2D heterostructures with vdW interlayer interactions.…”
Section: Fabrication Of 2d Heterostructuresmentioning
confidence: 99%
“…The synthesis strategies [93][94][95][96] devoted to the preparation of 2D heterostructures could be classified into three main kinds, including exfoliation and transfer method, [97,98] chemical vapor deposition (CVD) method, [99,100,101] and physical vapor deposition method (PVD). [29] The exfoliation and transfer method is dedicated to the exploration of vertical 2D heterostructures with vdW interlayer interactions.…”
Section: Fabrication Of 2d Heterostructuresmentioning
confidence: 99%
“…[7] Consequently, bathocuproine (BCP) and C 60 are usually used as blocking layers to decrease the dark current. [10][11][12] Additionally, these low-mobility organic layers would significantly increase the difficulty of transporting the charges generated by photons to the electrodes. [10][11][12] Additionally, these low-mobility organic layers would significantly increase the difficulty of transporting the charges generated by photons to the electrodes.…”
Section: Doi: 101002/aelm201800237mentioning
confidence: 99%
“…The decreased sensitivity is mainly caused by the absorption depth. [12] However, for organometallic perovskites, the high defect tolerance could protect the device from radiation hardness. Consequently, 88.5% gamma photons pass through the device.…”
Section: Doi: 101002/aelm201800237mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the preparation of high quality MoS2-MoSe2 [55] (Figure 3a,b,c), MoSe2-WS2 [56], WSe2-SnSe2 [57], and MoS2-WSe2 [58,59] was achieved by this method as well. Shi et al [60] reported the fabrication of SiC with WSe2 surface flakes whose thickness ranged from several layers to several microns by this method and further studied the effects of energetic ion irradiation on such heterostructure. Lopez-Sanchez et al [61] showed the realization of electroluminescent devices and solar cells based on vertical heterojunctions composed of n-type monolayer MoS2 and p-type silicon.…”
Section: Mechanical Exfoliation Methodsmentioning
confidence: 99%